A Design Remote Control System to Feed Birds Using ESP8266 - Saidatin, Naili; Nurmuslimah, S.; Bagus, P. (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Keeping lovebirds at home becomes one of hobbies that is fascinating to some people. Keeping them as pets means educate us to be regular people, particularly related to the process of food provision. Innovation on feeding bird is required such as automatic feeding which can be controlled from far areas. It will be very beneficial when the lovebird keepers are not at home. Therefore, this study develops at designing an automatic system for feeding birds completed with remote control. For this reason, the researcher used ESP8266 connected to NODEMCU as the hardware and BLYNK server as the control bridge of internet. The data would then be transmitted from smartphone to esp8266 system to control the feeding process. In the context of feeding process, the researcher used RTC-clock owned by BLYNK server to substitute RTC as the hardware. Automation system of food provision was carried out by synchronizing the data of hours from the users. The research data were used to design feeder bucket which could give food around 7.2-52.8 grams and feeder bucket for accommodating food about 6.2-48.3 grams. The results of control and connection via BLYNK server demonstrated that 90% data were connected. In terms of data accuracy, this automatic feeder could be accurately 100% successful in a certain time.